Solar photovoltaic-assisted DC vapour compression with a low-cost ice gel thermal battery for off-grid building cooling - Jarimi, Hasila; Wan Roshdan, Wan Nur Adilah; Abdullah, Amirudin; Zheng, Tianhong; Zhang, Yanan; Razak, Tajul Rosli; Riffat, Saffa; Ahmad, Emy Zairah; Abd Rahman, Noor Muhammad; Jamaludin, Mohd Haikal (Elsevier Ltd, 2024)
In off-grid areas where extending the grid is costly, traditional AC powered air conditioning units pose challenges for off-grid photovoltaic PV setups due to expensive inverters and battery storage. This leads to an interest in cost-effective solar-driven DC cooling system. However, its efficiency depends on solar energy availability with limited operation during low solar radiation. This study proposes a solar PV-driven DC vapour compression system with variable refrigerant flow (VRF) and low-cost organic phase change material (PCM) ice gel storage. Preliminary experimental work determined the best operational mode namely, Mode A (PV + Thermal Battery), Mode B (PV-electrical battery-3h + Thermal Battery), Mode C (PV-grid + Thermal Battery), and Mode D (Grid + Thermal Battery). Key performance parameters include the Performance Quality Factor of the PV-powered system SFPVVC, and levelized cost of cooling (LCOC). Mode B was found the best, and due to the system's complex dynamic variation with environmental parameters, a novel simulation approach combining artificial neural network (ANN) and TRNSYS was developed and experimentally validated. Thermal comfort is crucial for healthcare facilities as it promotes patient well-being, enhances staff performance, and is vital for infection control, thus a rural healthcare facility in Malaysia was selected for the simulation case-study. Mode B showed at least 50 % higher SFPVVC compared to grid reliance, with superior LCOC performance, ensuring sustainable cooling despite limited electricity supply. The low-cost ice gel thermal battery reduced the system cost to 0.06 USD/kWh compared to 0.56 USD/kWh without it and 1.01 USD/kWh with grid extension. These findings offer insights for implementing similar sustainable cooling systems in rural areas.